The Effect of TikTok Social Media Use on the @asisichannel account on Students’ Historical Awareness in History Class Grade X at SMKS PGRI 1 in Serang City: Pengaruh Pemanfaatan Media Sosial Tiktok Pada Akun @asisichannel Terhadap Kesadaran Sejarah Siswa Dalam Pembelajaran Sejarah Kelas X di SMKS PGRI 1 Kota Serang - Arif Permana Putra; Agus Rustamana; Atik Rositah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This article aims to determine the impact of TikTok social media usage on the @asisichannel account on students' historical awareness in history learning in Grade X at SMKS PGRI 1 Kota Serang. The method used is quantitative, with a non-probability sampling technique for data collection. This research was conducted in the X grade Computer Network Engineering class with 36 students. The instrument used was a questionnaire with 24 statements to explain variable X and 23 statements to explain variable Y. Based on the research results, there is an influence between variable X and variable Y, as evidenced by the results of the simple linear regression analysis test, which obtained a sig. 0.000 ˂ 0.05, which means that variable X influences variable Y, and the hypothesis test (t-test) showed a sig. value of 0.000 ˂ 0.05, so Ha was accepted and H0 was rejected. This proves that there is a significant influence of the use of TikTok social media on the @asisichannel account on students' historical awareness. The social media platform TikTok @asisichannel can be recommended as a learning medium for history lessons because the design and appeal of its content can attract students' interest in learning, thereby increasing the effectiveness and impact of using TikTok on history lessons.